Contribution of 3-D computer-assisted reconstructions to the study of the initial steps of mouse odontogenesis - Peterková, R; Peterka, M; Vonesch, J L; Ruch, J V (The International journal of developmental biology, 1995)
The specific arrangement of mouse dentition in each dental quadrant (1-0-0-3) is supposed to result from the initiation of two independent dental laminae--one for the incisor and one for the three molars. In order to verify whether the adult mouse dental pattern really corresponds to the initial patterning, an analysis of development of the mouse antemolar part of the upper dental quadrant was performed in 10-13 day embryos using histological sections and computer-assisted 3-D reconstructions. Six primary dental laminae contributed to the formation of the upper incisor anlage, which is, therefore, a structure of multiple origin. In contrast to the lower diastema, where only a low epithelial band extended mesially from the first lower molar in 12-13 day embryos, in the upper diastema a dental lamina existed interconnecting transiently the incisor and molar anlagen and giving rise to 3 distinct epithelial rudiments. The rudiments exhibited growth retardation and regressed after reaching a maximum at the bud stage. Our results showed a discrepancy between the embryonic and adult dental patterns in the mouse upper jaw. The specific arrangement of the mouse dentition implied a reduction of the embryonic dental anlagen, which was achieved either by their integration into the one incisor primordium or regression in the prospective diastema. Odontogenesis in the mouse upper jaw provides a model of hypodontia of evolutionary origin, which can be employed in molecular studies of the control mechanisms of initiation, spatial organization and specific morphogenesis of teeth.
Keywords: myši; Image Processing, Computer-Assisted; Animals; Diastema; řezáky; odontogeneze; zvířata; Incisor; Epithelium; Mice; Odontogenesis; diastema; epitel; Mesoderm; počítačové zpracování obrazu; mezoderm